Successfully Treated Calcific Uremic Arteriolopathy: Two Cases of a High Anion Gap Metabolic Acidosis with Intravenous Sodium Thiosulfate - Joshua L. Rein; Kana N. Miyata; Kobena A. Dadzie; Steven J. Gruber; Roxana Sulica; James F. Winchester (Case Reports in Nephrology)
Calcific uremic arteriolopathy (CUA) is a rare and potentially fatal disorder of calcification involving subcutaneous small vessels and fat in patients with renal insufficiency. We describe the successful use of intravenous sodium thiosulfate (STS) for the treatment of CUA in two patients. The first case was complicated by the development of a severe anion gap metabolic acidosis, which was accompanied by a seizure. Both patients had complete wound healing within five months. Although STS should be considered in the treatment of CUA, little is known about pharmacokinetics and additional studies are required to determine dosing strategies to minimize severe potential side effects.